Strategi Implementasi Kurikulum pada Lembaga Pendidikan Islam untuk Meningkatkan Literasi Keislaman Siswa - Ittaqillah Haisuma Kunta; Ida Kusumawati; Muthi’ah Rahman; Siti Khofsah; Annisa Tri Ananda Dewi; Uryatul Hikmah; Badrul Mudarris (CV. Laskar Karya, 2025)
The implementation of the curriculum in Islamic educational institutions plays an important role in shaping the character and Islamic competence of students, especially at the elementary school level. This study aims to describe curriculum implementation strategies in improving students’ Islamic literacy, which includes their ability to read, understand, and practice Islamic teachings through both formal and non-formal learning activities. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation. The findings show that curriculum implementation is carried out through the integration of Islamic values into all subjects, the implementation of habituation programs such as daily prayers, shalat dhuha, and Qur’an recitation (tadarus), and the strengthening of extracurricular activities such as Qur’an Reading and Writing (BTQ) and Islamic studies. Teachers serve as role models and facilitators in creating a religious, dynamic, and inclusive learning environment, while support from the principal, school committee, and parents reinforces the effectiveness of these strategies. A well-directed and sustainable curriculum implementation has been proven to contribute to the improvement of students’ Islamic literacy, in terms of understanding religious teachings, Qur’an reading ability, and religious behavior in daily life.